2005
DOI: 10.1177/154193120504901725
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone-Conduction Headsets for Use in Multitalker Communication Environments

Abstract: Standard audio headphones are useful in many applications, but they cover the ears of the listener and thus may impair the perception of ambient sounds. Bone-conduction headphones offer a possible alternative, but traditionally their use has been limited to monaural applications due to the high propagation speed of sound in the human skull. Here we show that stereo bone-conduction headsets can be used to provide a limited amount of interaural isolation in a dichotic speech perception task. The results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…For instance, instead of delivering information through con ventional headphones, auditory information may be conveyed to the cochlea via bone conduction. Bone conduction delivers auditory stimuli without ob structing the external ear, allowing the user to also hear surrounding sounds (MacDonald et al, 2006;Walker et al, 2005). Although studies explicitly assessing possible interference between substituted information delivered via bone conduction and the surrounding sounds are required, the use of this tech nology appears promising.…”
Section: Device Ergonomics and Functionalitymentioning
confidence: 97%
“…For instance, instead of delivering information through con ventional headphones, auditory information may be conveyed to the cochlea via bone conduction. Bone conduction delivers auditory stimuli without ob structing the external ear, allowing the user to also hear surrounding sounds (MacDonald et al, 2006;Walker et al, 2005). Although studies explicitly assessing possible interference between substituted information delivered via bone conduction and the surrounding sounds are required, the use of this tech nology appears promising.…”
Section: Device Ergonomics and Functionalitymentioning
confidence: 97%
“…Moreover, they ensure that the pinna and ear canal remain unobstructed (Walker & Stanley, 2005). Generally, their use has been restricted to monaural applications, although investigations for their application in audio display designs is ongoing (Tonndorf, 1972;Walker & Stanley, 2005). While headphone-based systems offer potential benefits, there are shortcomings to their use as well.…”
Section: Headphone-based Systemsmentioning
confidence: 98%
“…Bone conduction headsets which allow sound to be delivered to the user via direct application of vibrators to the skull are small, comfortable, and provide the privacy and portability offered by traditional headphones. Moreover, they ensure that the pinna and ear canal remain unobstructed (Walker & Stanley, 2005). Generally, their use has been restricted to monaural applications, although investigations for their application in audio display designs is ongoing (Tonndorf, 1972;Walker & Stanley, 2005).…”
Section: Headphone-based Systemsmentioning
confidence: 99%
“…Walker, Stanley, Iyer, Simpson, and Brungart (2005) conducted a study on the application of bone conduction headphones in a multi-talker environment to find its advantage in a multi-channel communication system. The study concluded that binaural separation was possible using stereo bone conduction headphones.…”
Section: Literature Reviewmentioning
confidence: 99%